PERBANDINGAN PERTUMBUHAN JARINGAN RE-EPITELISASI PERAWATAN LUKA MENGGUNAKAN BALUTAN LUKA HYDROCOLLOID DAN NACL + GAUZE PADA PENDERITA ULKUS DIABETIK DI RS. BHAYANGKARA MAKASSAR (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2019)
Diabetic foot is a disorder of the lower leg due to uncontrolled diabetes mellitus, which can be caused by peripheral vascular disease or by neuropathy but often by both. The choice of dressing is based on the principle of keeping the wound moist with the properties of a moist dressing. The purpose of this study was to see and compare the growth of re-epithelialized tissue in diabetic foot ulcers treated using modern hydrocolloid dressing techniques and conventional NaCl + Gauze techniques. The research design used was a quasy experimental design with a pre-test and post-test nonequivalent control group design. The population in this study were diabetic foot ulcer sufferers, using the Accidental Sampling technique, dividing 8 respondents into 2 groups, 4 respondents using hydrocolloid dressings and 4 respondents using NaCl + Gauze dressings. The results were obtained from 8 respondents after being treated for 15 days, the mean values ??were obtained for the Hydrocolloid group n1 = 1.87 cm, n2 = 1.24 cm, n3 = 0.52 cm, n4 = 2.64 cm, while in the control group (NaCl + Gauze) the average values ??were n5 = 0.34 cm, n6 = 0.6 cm, n7 = 0.31 cm, n8 = 0.37 cm. The results of data analysis using the independent t-test statistical test, obtained significant results, where the value of P <0.05 or P = 0.030. it can be concluded that Ha is accepted, namely diabetic ulcers treated using Hydrocolloid wound dressings show a better re-epithelialization thickness than diabetic ulcers treated using NaCl + Gauze. From the results of this study it is hoped that the institution can use the modern hydrocolloid dressing technique as an SOP for wound care